2015
DOI: 10.1523/jneurosci.4645-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Integration of Motion Information in Children With Autism

Abstract: To judge the overall direction of a shoal of fish or a crowd of people, observers must integrate motion signals across space and time. The limits on our ability to pool motion have largely been established using the motion coherence paradigm, in which observers report the direction of coherently moving dots amid randomly moving noise dots. Poor performance by autistic individuals on this task has widely been interpreted as evidence of disrupted integrative processes. Critically, however, motion coherence thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
140
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(163 citation statements)
references
References 58 publications
20
140
2
Order By: Relevance
“…Despite the improved averaging ability, however, the children with ASD performed comparably to typical children in the standard motion coherence task. Manning et al (2015) drew two main conclusions from these data. Firstly, children with ASD outperformed typically developing children in the high-variability motion direction task, suggesting enhanced integration of local motion in ASD.…”
Section: Robustness In Perception and Actionmentioning
confidence: 98%
See 3 more Smart Citations
“…Despite the improved averaging ability, however, the children with ASD performed comparably to typical children in the standard motion coherence task. Manning et al (2015) drew two main conclusions from these data. Firstly, children with ASD outperformed typically developing children in the high-variability motion direction task, suggesting enhanced integration of local motion in ASD.…”
Section: Robustness In Perception and Actionmentioning
confidence: 98%
“…The authors used an adaptive staircase method in all three tasks to estimate thresholds. Manning et al (2015) found that children with ASD, compared to the typically developing children, were as sensitive to directional differences when all elements moved in the same direction (no-variability). Crucially, the children with ASD proved more sensitive to the average direction in the presence of directional variability (high-variability) than the typically developing children.…”
Section: Robustness In Perception and Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…One final note is that the contribution of one group to the IMFAR symposium in 2014 is published elsewhere (Manning et al 2015), and further contributes to the debate around local versus global processing of visual motion in ASD.…”
mentioning
confidence: 99%